Allosteric regulation of pyruvate kinase from Mycobacterium tuberculosis by metabolites - Snášel, Jan; Pichová, Iva (Biochimica et biophysica acta. Proteins and proteomics, 2019)
Mycobacterium tuberculosis (Mtb) causes both acute tuberculosis and latent, symptom-free infection that affects roughly one-third of the world's population. It is a globally important pathogen that poses multiple dangers. Mtb reprograms its metabolism in response to the host niche, and this adaptation contributes to its pathogenicity. Knowledge of the metabolic regulation mechanisms in Mtb is still limited. Pyruvate kinase, involved in the late stage of glycolysis, helps link various metabolic routes together. Here, we demonstrate that Mtb pyruvate kinase (Mtb PYK) predominantly catalyzes the reaction leading to the production of pyruvate, but its activity is influenced by multiple metabolites from closely interlinked pathways that act as allosteric regulators (activators and inhibitors). We identified allosteric activators and inhibitors of Mtb PYK originating from glycolysis, citrate cycle, nucleotide/nucleoside inter-conversion related pathways that had not been described so far. Enzyme was found to be activated by fructose-1,6-bisphosphate, ribose-5-phosphate, adenine, adenosine, hypoxanthine, inosine, L-2-phosphoglycerate, l-aspartate, glycerol-2-phosphate, glycerol-3-phosphate. On the other hand thiamine pyrophosphate, glyceraldehyde-3-phosphate and L-malate were identified as inhibitors of Mtb PYK. The detailed kinetic analysis indicated a morpheein model of Mtb PYK allosteric control which is strictly dependent on Mg2+ and substantially increased by the co-presence of Mg2+ and K+.
Keywords: Metabolites; metabolomika; Catalysis; Allosteric Regulation; Pyruvate Kinase; Pyruvate kinase; Metabolism; Glycolysis; alosterická regulace; kinetika; pyruvátkinasa; Ions; glykolýza; Metabolomics; Allosteric regulation; Kinetics; katalýza; Mycobacterium tuberculosis